Effectiveness of Postoperative Radiotherapy on Atypical Meningioma Patients: A Population-Based Study - Zeng, Qiang; Shi, Feina; Guo, Zhige (Frontiers in Oncology, 2019)
Purpose: It is controversial whether atypical meningioma patients undergoing gross-total resection (GTR) can benefit from postoperative radiotherapy (PORT). This study aimed to investigate the effectiveness of PORT on atypical meningioma patients. Methods: Patients diagnosed with atypical meningioma from 2008 to 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. The Kaplan–Meier survival curves were generated, and the log-rank test was used to compare the differences among groups. Univariable and multivariable COX regressions were conducted for survival analyses. Results: A total of 1014 patients were enrolled. The 5-year survival rate of the overall patients was 79.0%. PORT was performed in 315 (31.1%) patients. The utilization rates of PORT in patients undergoing GTR and undergoing subtotal resection (STR) were 26.7% and 42.2%, respectively. For patients undergoing STR, log-rank test showed that overall survival (OS) time was significantly longer in patients receiving PORT than those not (p = 0.026). For patients undergoing GTR, OS time did not show significant association with PORT (p = 0.339). In addition, patients undergoing STR with PORT had no significantly different OS time compared with those undergoing GTR with PORT (p = 0.398). Multivariable Cox regression analysis showed that receipt of PORT (p = 0.187) was not an independent predictor of OS after adjustment. Conclusion: PORT may not prolong the OS in atypical meningioma patients undergoing GTR. However, patients undergoing STR may benefit from PORT and achieve similar OS to those undergoing GTR.